Penerapan Genggam Bola Karet dan Mindfulness Therapy Meningkatan Kekuatan Otot dan Mengurangi Kecemasan Lansia Stroke di Kesejahteraan Sosial Paduwau - Febiana Nona Batang; Sudarwati Nababan (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Background: Stroke is damage to brain tissue caused by a sudden reduction or cessation of oxygen supply in the blood. Brain tissue that experiences a decrease in oxygen supply in the blood will die and no longer function. Stroke can cause weakness in muscles or body movement coordination. Elderly stroke sufferers feel low self-esteem due to disability and anxiety about death. One of the non-pharmacological techniques to overcome muscle weakness and overcome anxiety is rubber ball grip therapy and mindfulness therapy. The purpose of this case study is to determine the effect of Rubber Ball Grasp and Mindfulness Therapy on muscle strength and anxiety levels. The method used in this case study design is a nursing care process approach. The subjects in this case study were 2 patients, obtained from inclusion and exclusion criteria, data collection using Manual Muscle Testing (MMT) and the Hamilton Anxiety Rating Scale (HARS). The results of the case study show that the average muscle strength and anxiety level after being given the rubber ball grip therapy intervention for 6 days and mindfulness therapy for 3 days experienced changes from muscle strength without movement, muscle contractions could be felt/visible to normal full movement against gravity. and combat minimal resistance and severe to moderate levels of anxiety. In conclusion, there is an influence of rubber ball handheld therapy and mindfulness therapy on stroke elderly in the Paduwau Maumere Elderly Social Welfare Section.